Common management of investment capital from different investors in Mudarabah: scope of validity and consequences in Islamic law - Sadique, Muhammad Abdurrahman (Zesdyzar Rokman Resources, 2013)
Elements of both mudārabah (fund management) as well as shirkah (partnership) in Islamic law are reflected in the operation of investment accounts offered by Islamic financial institutions. A number of partners pooling their funds together for running a business operation is possible under shirkah. Similarly, mixing mudārabah capital with funds of the mudārib (entrepreneur/fund manager) could be valid according to the majority of schools with express permission from the investor. In mudārabah, the schools of Islamic law have recognized the validity of several parties jointly investing funds with a common mudārib through a single contract. Such investment should take place jointly on a single occasion, so that the tenure of mudārabah could commence with regard to all capitals at the same time. Where the mudārib accepts investments from different individuals through individual contracts, the majority of schools require that the business of each capital be managed separately. This restriction is due to fundamental anomalies that may result from mixing different capitals, which, having mobilized in business separately, could be at different stages of profit or loss. However, jurists of the Hanafi school appear to have allowed the mudārib to mix funds of different investors together with their permission. This could possibly indicate permissibility of mixing funds invested at different stages when overall permission had been obtained. The procedure adopted in this regard in the investment accounts run by Islamic banks requires further research and scrutiny.